Baby Simulacra. Semiotics of Puppies in Cinema as Axiology Incubators - Surace, Bruno (E|C, 2020)
The aim of this essay is to trace a semiotics of the cinematographic puppy as a actantial figure in which axiologies and ideologies are encapsulated at the same time. In order to do so, we will use textual analysis limited on the one hand to the universe of horror cinema, transversely dotted with puppies, and on the other hand to cinema for children, who live the ultimate phase of puppiness. The textual analyses will make it possible to identify the distinctive traits of the puppy's imagination, understood as an archetypal figure that is uncontaminated, but also and above all disturbing because it is substantially inscrutable, to identify formal stylistic features and narrative programs that make it so, and to grasp the specifics in terms of cultural semiotics and psychosemiotics.